Caracterización de aislamientosde Fusarium spp de plantas de tomate (Solanum lycopersicum L) en la finca elCarrizal – México. - Enríquez Acosta, Emmanuel Alexander (2019)
In the present study, it was carried out with the objective of characterizing pathogenic isolated of Fusarium spp. from tomato plants on the farm ¨El Carrizal¨ Mexico. For which a sampling was carried out for the collection of plants with symptoms of Fusarium infection then it was processed to isolate the pathogen and obtain the pure culture to evaluate the coloration, size, mycelial growth rate, texture, abundance of spores, morphological characteristics mainly of micro and macroconidia. It was determined that there is great variability in terms of the variables evaluated, for example, in the colorations ranged from whitish to violet red and wine red. Fusarium spp is a fungus that presents the possibility of developing in PDA medium and achieving adequate development. Regarding morphology, the presence of microscopic structures typical of Fusarium spp. Curved or semi-curved macroconidia were observed with 3-5 septa with narrow, papillary or blunt-type apical cells, predominantly reniform and fusiform microconidia, from zero to 1 septum, mostly from monofiálides. In some isolates, the production of paired clamidospores was confirmed, presenting great variability, in terms of coloration, texture, speed of growth and shape of morphological structures, and Koch's postulates were verified.